(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
In this paper I would like to begin to open up some of the thinking of French philosopher Simone Weil and consider how it might inform our work as existential psychotherapists. It seems to me that this (female) thinker, whose thought is deeply existential, has generally been overlooked in the established canon of existential philosophers. And yet she was once described by Albert Camus as ’the only great spirit of our time’. I will propose that Weil has something to offer us, particularly in her thinking on the nothingness (which she terms God) at the heart of Being and her concept of affliction, and, most challenging of all, her assertion that beauty can exist in the deepest affliction. I will begin by drawing some parallels with other existential thinkers, most notably Heidegger, to illustrate how the basic tenets of Weil’s thought are deeply existential. I will then offer up some glimpses of Weil’s thinking, noticing how it appears to us and penetrates us through the language of poetry, that is to say most particularly metaphor, and I will demonstrate with two case vignettes how her thought can enrich and enlighten our existential work with clients.